2007
DOI: 10.1029/2007gl029893
|View full text |Cite
|
Sign up to set email alerts
|

Bromoform in tropical Atlantic air from 25°N to 25°S

Abstract: Atmospheric mixing ratios of bromoform (CHBr3) measured over the eastern Atlantic Ocean were enhanced (4 to 13 pptv) between 8–25°N, 17–21°W, in air masses advected over the NW African coast/upwelling zone. The highest mixing ratios at 8–10°N were associated with a biomass burning plume from the African savannah belt. Airborne samples taken over Nigeria showed however that biomass burning here is not a source of CHBr3. Previously reported water samples taken near to the NW African upwelling zone do not support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
(36 reference statements)
4
26
0
1
Order By: Relevance
“…For example, a study by Carpenter et al (2007) measured CHBr 3 concentrations over the eastern Atlantic Ocean between 25 • N and 25 • S, ranging from a minimum of 0.2 ppt to a maximum of 13.3 ppt at 9.5 • N. Similar maximum mixing ratios of CHBr 3 over the tropical northern Atlantic Ocean were observed by Class and Ballschmiter (1988) (14 ppt) and Quack et al (2004) (25 ppt). In the eastern Atlantic Ocean, the bioactive Mauritanian upwelling has been suggested as an important source of reactive organic bromine (Quack et al, 2007a;Carpenter et al, 2007), though ship-borne measurements taken in May/June 2007 found no instances of high atmospheric CH 2 Br 2 or CHBr 3 concentrations (Carpenter et al, 2009). Quack et al (2007b) found that their atmospheric measurements over the tropical North Atlantic Ocean could not be explained solely by emissions from the Mauritanian upwelling and suggested that a West African continental source was necessary.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, a study by Carpenter et al (2007) measured CHBr 3 concentrations over the eastern Atlantic Ocean between 25 • N and 25 • S, ranging from a minimum of 0.2 ppt to a maximum of 13.3 ppt at 9.5 • N. Similar maximum mixing ratios of CHBr 3 over the tropical northern Atlantic Ocean were observed by Class and Ballschmiter (1988) (14 ppt) and Quack et al (2004) (25 ppt). In the eastern Atlantic Ocean, the bioactive Mauritanian upwelling has been suggested as an important source of reactive organic bromine (Quack et al, 2007a;Carpenter et al, 2007), though ship-borne measurements taken in May/June 2007 found no instances of high atmospheric CH 2 Br 2 or CHBr 3 concentrations (Carpenter et al, 2009). Quack et al (2007b) found that their atmospheric measurements over the tropical North Atlantic Ocean could not be explained solely by emissions from the Mauritanian upwelling and suggested that a West African continental source was necessary.…”
Section: Introductionsupporting
confidence: 59%
“…where observed fluxes of CHBr 3 are more than twice the values in MON at around 30-40 nmol m −2 day −1 (Quack et al, 2007a;Carpenter et al, 2007). However, an extra experiment performed using a CHBr 3 flux of 40 nmol m −2 day −1 over the upwelling region (16-20 • W, 14-20 • N) still does not reproduce the measured high concentrations at Cape Verde.…”
Section: Comparison Of Measured and Modelled Bromocarbon Concentrationsmentioning
confidence: 71%
“…This suggests that biomass burning is a possible additional source of CHBr 3 . High mixing ratios of CHBr 3 associated with African savannah biomass burning plumes were documented in Carpenter et al (2007). The lack of biomass burning emissions can also explain the lack of variability in simulated CHBr 3 mixing ratios compared with the high variability observed in the INTEX-A mission, during which significant biomass burning plumes were sampled (Turquety et al, 2007;Liang et al, 2007).…”
Section: Chbrmentioning
confidence: 81%
“…Quack and Wallace, 2004), except for certain upwelling regions (e.g. Class and Ballschmiter, 1988;Quack et al, 2004;Carpenter et al, 2007), where a high abundance of phytoplankton is expected to account for strong emissions of these bromocarbons. Several studies (e.g.…”
Section: Introductionmentioning
confidence: 99%